APPLICATION OF FERTILIZER AND BREEDING PROGRAMS IN SALES KUD USING VISUAL BASIC WIROTO 6.0 - Rita Riyanti Pipit; Ire Puspa Wardhani, SKom, MMSI (Jurnal Sistem Informasi, 2005)
Village Cooperative is a business unit together Based on equality of rights and obligations to realize the interests of the community. Data recording system used in the cooperative is still using a manual method. Of course this is less efficient, because it will often cause problems such as problems in the writing and the delay of information, especially concerning the problem statement.This program includes the application of creditpayment information each time transaction, so it can be more easily and to optimize control of every month. With the help of supporting applications created with Microsoft Visual Basic 6.0 is expected to ease in knowing the credit payment information.